NAVIGATING EXTREME VOLATILITY: RISK-ADJUSTED PERFORMANCE OF INDONESIAN SHARIA FUNDS (2020-2024) - Nur, Nur Syifa Ullida; Farhadi Arifiansyah (I-Finance Journal, 2025)
This study aims to analyze the development of Net Asset Value (NAV) and evaluate the performance of Islamic equity mutual funds in Indonesia during the 2020–2024 period using the Sharpe Ratio method as a risk-adjusted performance measure. The study population comprises all Islamic equity mutual funds registered with the Financial Services Authority (OJK) from 2020 to 2024. The research sample utilized aggregate data of national Islamic equity mutual funds published by the OJK in the form of monthly data over five years (60 observations), selected using purposive sampling based on the availability of NAV, return, and risk-free rate data. Data analysis was performed using descriptive statistics, Sharpe Ratio calculation, and One-Way ANOVA tests. The results indicate that the NAV of Islamic equity mutual funds increased from IDR 927.69 billion in 2020 to IDR 1,148.90 billion in 2024. However, the average Sharpe Ratio ranged from 0.05 to 0.25, indicating a low performance trend, with negative values observed in several periods. The ANOVA test showed no significant difference in performance across the years. The conclusion suggests that the performance of Indonesian Islamic mutual funds was suboptimal, and there were no significant performance differences during the 2020–2024 period.